Nutritional Intervention in Osteoporosis: An Overlooked Management in Primary Care - Muhammad Gifari Rasyidi; Mohammad Wibowo Ariyanto; Ahmad Fakar Sanusi Rasyid; Elvan Wiyarta (MEDICINUS, 2025)
Osteoporosis is a bone disease with a high global mortality rate. Typically, it affects adults and the elderly, particularly postmenopausal women. Normally, bone thinning and decreased bone mineral density are consequences of aging. Osteoporosis leads to significant decrease in quality of life and an increase in the incidence of fractures. In this condition, bone formation and resorption must be in balance for optimal bone remodeling. Numerous factors affect this mechanism, but one has frequently been overlooked: the deficiency of nutrients such as vitamin D, calcium, and other micronutrients that could help maintaining healthy bone remodeling. The effect of nutrition on bone formation and the prevention of bone loss is synergistic. Therefore, supplementation and nutritional sufficiency monitoring in individuals at risk for osteoporosis can be one prudent action. Most therapeutic focus in Indonesia remains exclusively concentrated on curative pharmacotherapy. This article aims to review the existing literature on nutritional interventions to prevent and slow the progression of the disease, as well as raising awareness regarding the urgency to take preventive measures in osteoporosis management.